Influence of charcoal residues and cattle manure on the development of faveira seedlings (Research, Society and Development, 2022)
The production of seedlings includes stages that may require greater or lesser financial investments, such as fertilization. One way to minimize costs is to use organic materials that can be rich in nutrients and physically condition the substrate. The objective of this study was to evaluate the performance of faveira seedlings (Enterolobium barnebianum) on substrates composed of bovine manure and biochar produced from trunk segments and branches of Lacre. The experiment was carried out in a greenhouse, using a completely randomized design, in a factorial scheme (5 x 5) treatments and five replications. The study factors were: five doses of ground biochar (0, 20, 40, 60 and 80 t ha-1) and five doses of bovine manure (0, 10, 20, 30 and 40 t ha-1). The characteristics evaluated were: shoot and root dry mass, total dry mass and the concentration of macro and micronutrients in the shoot. The application of doses above 40 t ha-1 of biochar negatively affected plant growth and decreased the concentration of P and Mn. On the other hand, it increased the concentration of Ca, Mg, K and Zn. As for manure, doses of 20 t ha-1 positively influenced the total dry matter of the plant. As for manure, doses of 20 t ha-1 positively influenced the total dry matter of the plant. Thus, the application of charcoal did not provide gains in seedling growth. Under the conditions of this work, it is recommended to use 20 t ha-1 of bovine manure in the composition of the substrate used for the production of faveira seedlings.